Late Relapses of Membranous Nephropathy: A Case Series. Issue 6 (24th June 2021) - Peleg, Yonatan; Bomback, Andrew S.; Canetta, Pietro A.; Radhakrishnan, Jai; Appel, Gerald B.; Ahn, Wooin
Visual Abstract: Abstract: Key Points: Primary membranous nephropathy can relapse after >5 years of achieving remission. Late relapse can occur even 36 years after initial manifestation. It has a favorable prognosis. Acknowledgment of this under-recognized form of membranous nephropathy may lead to early diagnosis of relapse, avoiding unnecessary workup. Background: Relapse of the nephrotic syndrome is co mmon among patients with primary membranous nephropathy (MN). Relapses of MN typically occur within a few years of achieving disease remission. There is limited description, to date, regarding patients with MN who have late relapse of MN, i.e., after >5 years of sustained disease remission. The objective of this case series was to report the clinical course of patients with MN who experience late relapse. Methods: We analyzed the patient database of the Glomerular Kidney Disease Center at Columbia University to identify patients seen at our center who had relapse of biopsy specimen–proven MN at least 5 years after achieving sustained disease remission. Results: We identified 16 patients with late relapse of MN. The median time in sustained remission before relapse was 10.2 (range, 7–29.0) years. Ten patients (63%) were diagnosed with late relapse on the basis of laboratory monitoring alone, without clinical symptoms of the nephrotic syndrome. Fourteen patients (88%) received immunosuppression during their initial presentation and late relapse. Patients had favorable long-term renal outcomes over a median 21 (range, 12–56) year follow-up period, with 14 patients (88%) in remission at study conclusion and a median decline in eGFR per year of −0.63 (range, −6.3 to 17.5) ml/min per 1.73 m 2 per year. Conclusions: This case series highlights a previously underappreciated, and likely rare, outcome of MN, namely, late relapse. Patients who experience late relapse, and who thus have a longer time in sustained remission, may have a more favorable long-term renal outcome.